Tenement house "Under the Golden Crown" in Wrocław - renovation of the peculiar monument = Kamienica "Pod Złotą Koroną" we Wrocławiu - renowacja osobliwego zabytku - Kirschke, Krystyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Among the many historic buildings in Wroclaw, there is a property address Rynek 29 - Oławska 2, that in 1970 entered in the register of monuments as a department store, earlier tenement house called "Under the Golden Crown". In the fact it was built in 1961 and it is neither a historical building nor department store. It is, spectacular example of creative retrospective, in the post-war reconstruction of Wroclaw.
Keywords: Wrocław; odbudowa powojenna; kamienica historyczna; kamienica mieszczańska; post-war reconstruction; historic tenement house